Microabrasion as an Effective Treatment for Severe Dental Fluorosis: Images in Medicine - Priyanka Rajesh Bhojwani; Anuja Ikhar; Aditya Patel; Manoj Chandak; Shweta Sedani (Journal of Clinical and Diagnostic Research)
A 28-year-old male presented to the dental clinic with white and brown discolourations, as well as hard, pitted areas on the enamel [Table/Fig-1,2], seeking aesthetic treatment. After obtaining a detailed medical history and performing a clinical examination, including electrical pulp testing and cold testing, a radiographic evaluation was conducted. The radiographs revealed no periapical lesions or caries, and no signs of resorption were observed in the teeth of interest. All the associated teeth were vital, with a healthy periodontium. The patient was diagnosed with severe enamel fluorosis, classified as grade 4 according to the Dean’s Index [1].